Socioeconomic status, depression, and incident arthritis in adults aged 50 years and over: Prospective evidence from six longitudinal aging studies - Lingyan Duan; Xiaomei Hu; Rui Qing; Rongyan Mou; Shuqi Chen; Zhu Lan; Fengming Zou (PLoS ONE, 2025)
Objectives To examine the independent and joint effects of socioeconomic status (SES) and depression with the risk of developing arthritis in adults aged 50 + . Methods This pooled study derived from six aging cohorts: the Health and Retirement Study in the United States (HRS), the Survey of Health, the Ageing and Retirement in Europe (SHARE), the English Longitudinal Study of Ageing (ELSA), the Korean Longitudinal Study of Aging (KLoSA), the China Health and Retirement Longitudinal Study (CHARLS), and the Mexican Health and Aging Study (MHAS). Cox proportional hazards models were applied to estimate independent and joint effects. Results Over a median follow-up of 5.9 years among 68,445 individuals, 14,476 newly developed arthritis. After adjusting for covariates, low level of education (low vs. high: HR = 1.25, 95%CI: 1.19, 1.32), wealth (first quartile vs. fourth quartile: HR = 1.23, 95%CI: 1.17, 1.29), SES (low vs. high: HR = 1.36, 95%CI: 1.26, 1.47) and depression (HR 1.37, 95% CI: 1.32, 1.42) were independently associated with increased risk of developing arthritis. Individuals with depression consistently exhibited the greater risk for incident arthritis across education, wealth, or SES levels. Within each depression level, higher socioeconomic position was associated with decreased risk. A dose-response analysis revealed a steady increase in hazard ratios (HRs) as depression scores escalated, underlining significant positive relationships. Conclusions This multinational study presents the significant interactions of SES and depression on the incidence of arthritis in middle-aged and older adults, underscoring the need for targeted preventive measures and healthcare policies to reduce the disease’s burden.